Changes in Siwang Ritual of the Bah Lut group at Kampung Bukit Terang, Kampar, Perak - Azam Abdelhakeem Khalid (Tanjong Malim, 2020)
Changes in Siwang Ritual of the Bah Lut group at Kampung Bukit Terang, Kampar, Perak by Azam Abdelhakeem Khalid